Incorporating costs, thresholds and spatial extents for selecting stream bioindicators in an ecotone between two Brazilian biodiversity hotspots. (August 2021) - Valente-Neto, Francisco; Martínez, Bruno Téllez; Hughes, Robert M.; Ferreira, Anderson; Severo-Neto, Francisco; Souza, Franco Leandro de; Souza, Rodolfo Portela; Escarpinati, Suzana Cunha; Roque, Fabio de Oliveira
Highlights: We evaluated aquatic assemblage responses to native riparian vegetation loss. We provided a framework that evaluates the cost-effectiveness of aquatic groups. EPT were more sensitive to native vegetation loss than fish for both spatial extents. EPT are most cost-effective for monitoring the effects of native vegetation loss. Abstract: Biomonitoring is critical for characterizing and monitoring status, spatial patterns, and long-term trends in the ecological condition of freshwater ecosystems. The selection of cost-effective bioindicators is a critical step in establishing such monitoring programs. Key indicator considerations are a reliable response to anthropogenic disturbances, a high benefit-cost-ratio and sensitivity at multiple spatial extents. We evaluated non-linear responses of Ephemeroptera, Plecoptera and Trichoptera (EPT) and fish to the effects of native vegetation loss within buffers of 100 m and 1000 m and assessed the sampling and processing costs involved for each assemblage. We sampled 37 neotropical stream sites in the Formoso River network, a karstic region of the Bodoquena Plateau, midwest Brazil, lying in the ecotone between the Cerrado and Atlantic Forest biological hotspots. We used TITAN (threshold indicator taxa analysis) to identify six indicator taxa, four EPT genera and two fish species. The four EPT genera had low negative thresholds to native vegetation loss, whereas the two fish species had positive thresholds. Thresholds were lower for the 100 m buffers than the 1000 m buffers for EPT. The most sensitive taxon ( Macronema, Trichoptera) had a threshold of 0% native vegetation loss in the 100 m buffers and nearly 40% in the 1000 m buffers. For taxa richness, we found no non-linear response to the effects of native vegetation loss for buffer extent nor assemblage. The total cost for EPT biomonitoring was US 3, 616; whereas for fish, the total was US 1, 901. Although fish were less expensive than EPT, they did not respond negatively to native vegetation loss and their positive threshold started at 48%, a level of vegetation loss that was highly disruptive of EPT. Therefore, we do not recommend using fish to monitor the effects of native vegetation loss on headwater streams in the Bodoquena Plateau. Although EPT monitoring costs 52% more than fish assemblage monitoring, it detected earlier impacts of the effects of native vegetation loss on stream biota, especially in the 100 m buffer. Therefore, EPT are more cost-effective early warning indicators for monitoring the effects of native vegetation loss in Bodoquena Plateau headwaters.